Evaluation of bilingual book for English language learning - Stella Prancisca; Cary Chappell (Journal of English Language Teaching Innovations and Materials (Jeltim), 2022)
This research develops a bilingual reading book that can benefit the students’ reading habits and English language skills. It was developed using an R&D model, namely ADDIE (analysing, designing, developing, implementing, and evaluating), focusing only on the last two stages. The research aimed to evaluate the book by gathering users’ perceptions before the book was launched publicly. To evaluate the book, 37 university students were involved by reading the book as an out-of-class reading. They were given a month to finish their reading. Then, they needed to complete five randomized questions after reading each chapter and a series of questionnaires after reading a whole book. Data from the quiz and the survey revealed positive results. Most of the students achieved a high score on the quiz. They also reported the suitability of the book’s language and topics with their current English level. Nonetheless, a few useful improvements were addressed related to image and layout.